Supermarket Loyalty Card Data for Delivering and Evaluating Dietary Interventions: A Narrative Review - Burgess, Romana; Suhag, Alisha; Skatova, Anya (International Journal of Population Data Science, 2026)
Objective Loyalty card data can provide valuable insights into food purchasing behaviours, offering a scalable tool to evaluate food choice in a real-world retail setting. This narrative review examines how such data have been used to deliver and assess dietary interventions. Methods We conducted a narrative synthesis of studies using loyalty card data to deliver or evaluate dietary interventions. Eligible studies were identified as a subset of a previously published scoping review of loyalty card data in health research, which involved systematic searches of MEDLINE, EMBASE, PsycINFO, and Scopus using keywords related to shopping, loyalty cards, and health. Searches were conducted in August 2024, with a final search in February 2025. Additional studies were identified through manual searches of reference lists for the purpose of this review. Results We found 15 studies evaluating dietary interventions using loyalty card data. Studies implemented a variety of intervention approaches, including price promotions, point-of-purchase nudges, educational messaging, and targeted feedback. The effectiveness of these were mixed, with some showing promising changes in purchasing patterns, and others limited by issues such as displacement effects and missing data. In addition, samples were biased towards female participants and older adults. Yet, loyalty card data enable longitudinal analysis, capture whole-basket purchases, and reduce reliance on self-report, positioning them as a valuable tool for use within dietary interventions. Conclusion Loyalty card data represent a promising tool for evaluating dietary interventions in real-world settings, offering granular insights into purchasing behaviour. However, several limitations were identified, including incomplete coverage across retailers and limited context about purchases. Linking loyalty card data with complementary datasets and using them to support personalised feedback may help address limitations, continuing to enhance their value for policy-relevant interventions.